ROLE OF RETINOID, CALSIUM, AND VITAMIN D IN BREAST CANCER PREVENTION - Adi Kusuma, I Gusti Agung Indra; Wahyuniari, Ida Ayu Ika (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Breast cancer is a malignant tumor cells that attack the cells of the breast. The excess free radicals in the body can lead to the process of the formation of breast cancer. Antioxidants are substances that are needed by the body to arrest radicals. By consuming antioxidants to taste can reduce the risk of the occurrence of cancer . Retinoid, calcium, and vitamin D is one of the antioxidant that can prevent breast cancer
Keywords: Retinoid, Calcium, Vitamin D, Breast Cancer